Fermentative properties of starter culture during manufacture of kefir with new prebiotics derived from lactulose. (June 2019) - Delgado-Fernández, Paloma; Corzo, Nieves; Lizasoain, Silvia; Olano, Agustín; Moreno, F. Javier
Abstract: The fermentation properties of a starter culture during kefir manufacture was studied with the inclusion of one emerging lactulose-derived oligosaccharide prebiotic and with the well-recognised galactooligosaccharide and lactulose prebiotics at different doses (2 and 4%). Microbial growth, glycerol, lactic and citric acids and short-chain fatty acids and carbohydrate utilisation during fermentation and cold storage of control and prebiotic supplemented kefirs were determined. Prebiotic levels remained unaltered during fermentation (24 h) and storage (28 days), with the exception of a decrease (7.3%) of lactulose in kefir with 4% prebiotic. Consequently, the viability of lactic acid bacteria and yeasts, as well as the pH or level of fermentation metabolites was similar for all kefirs. Therefore, our data highlight the suitability of kefir as a matrix for the consumption of a variety of prebiotics, including that of novel synthesis as lactulose-derived oligosaccharides, widening their potential food uses and applications.